What drives regional business cycles? The role of common and spatial components - Christian Dreger; Konstantin Kholodilin; Michael Artis (European Regional Science Association (ERSA), 2010)
The degree of comovement of economic activity across states or regions is an issue of utmost importance to policymakers. Asymmetric business cycles are often seen as an impediment to the formation of a common currency area. However, it has been argued that a common monetary policy in itself could reduce the cyclical asymmetry. We examine real business cycle convergence for 41 euro area regions and 48 US states. By looking at the regional dimension, a larger information set can be exploited and might offer new insights. Regions tend to be more open to trade than countries and the degree of specialisation is usually higher than at the national level. If diverging trends cancel out in the aggregate, policy conclusions based on national evidence could be misleading. Regional comovements may be caused not only by common business cycles, but also by other factors due to location. They can be linked to industrial structures and migration, but can also reflect non-economic factors like habits, heritage, and culture. Spatial spillovers have been largely neglected in previous studies, thereby creating omitted variable bias. A panel model allowing for spatial correlation is a convenient way to capture these effects. This analysis is also relevant from a monetary policy point of view. By comparing the synchronization of economic fluctuations in US states and comparable euro area regions, the perspectives of a common monetary policy in Europe can be assessed. The US provides a natural benchmark in this respect. Both the US and the euro area share similar socio-economic characteristics, regarding the size, the level of development, culture etc. The results obtained by a panel model with spatial effects indicate that the impact of national business cycles for the regional development has been rather stable over the past two decades. Hence, a tendency for convergence in business cycles often detected in country data is not confirmed at the regional level. The pattern of synchronization across the euro area is similar to that across US states. Although cyclical heterogeneity is detected, it does not indicate a serious impediment to a common monetary policy of the ECB.
Keywords: E32; C51; E37; 330; Business cycle convergence; spatial correlation; spatial panel model